Analisis Perlakuan Pajak Pertambahan Nilai (PPN) atas Jasa Outsourcing Berdasarkan Management Fee dan Total Tagihan - Intan Paujijah; Riyandi Nur Sumawidjaja; Yoyo Sudaryo (PT Ilmu Data Indonesia, 2026)
This study analyzes the treatment of Value Added Tax (VAT) on security outsourcing services provided by PT Karya Cahaya Anue by comparing the tax base (DPP) calculated from the management fee versus the total invoice value. Outsourcing service billing typically consists of two cost groups: labor-related costs (salary, BPJS, THR, uniforms, and operational costs) and the management fee received as compensation for managerial services. In practice, some service users request that VAT be calculated on the total invoice, while Minister of Finance Regulation (PMK) Number 83/PMK.03/2012 stipulates that when labor costs are clearly itemized separately from the service fee in the tax invoice, the VAT base should use the